Alternative introduction of milk formulas based on goat milk: discoveries and prospects - N. A. Geppe; M. D. Velikoretskaya; S. I. Shatalina; M. B. Aksenova; A. A. Venerin; A. V. Polyanskaya; S. N. Chebysheva (Лечащий Врач, 2022)
The optimal source of nutrition for a child of 1 year old is breast milk, which provides him physical and neuropsychic development. Human milk is known to contain high concentrations (5-20 g/l in mature milk) and a wide variety of oligosaccharides. A number of studies have shown that human milk oligosaccharides effectively stimulate the growth of bifidobacteria and shape the composition of the intestinal microbiota, reducing the risk of infections, as well as modulating immune cell function and providing nutrients for the development of the child. However, there are a number of reasons for transferring a baby to mixed or artificial feeding. In case of insufficient amount of milk or its complete absence from the mother, as well as with absolute contraindications to breastfeeding, the introduction of infant formula will be an effective alternative. It is necessary to make the right choice of the milk formula in order to prevent or correct the functional disorders of the gastrointestinal tract that have arisen earlier, which can be characterized as violations of the complex twoway connection between the central and enteral nervous system. Many studies have shown that goat's milk is more similar in composition to women's milk than cow's milk. Goat milk contains high levels of oligosaccharides compared to milk from other mammals and lower levels of αs1 casein. Goat milk is also reported to have significant lactoferrin N-glycan homology with human milk. Since 1906, goat's milk has been recognized as the best natural substitute for human milk and a source of proteins for various milk formulas, and since 2013 it has been included in the Directive of the European Commission. As a result of studies during 150 years, a large number of various oligosaccharides have been identified in goat milk, many of which are similar to breast milk oligosaccharides. Modern mixtures based on goat milk has a new formula now. The changes affected the protein and fat components of the formula. In all products the total amount of protein is reduced and the proportion of the serum fraction of protein is increased.